Ordinary differential equations: Second-order linear ODEs with constant coefficients
Discriminant equal to zero
Characteristic equation with discriminant equal to zero We consider the homogeneous second-order linear differential equation with constant coefficients, written in the form \[a\,\frac{\dd^2y}{\dd t^2}+b\,\frac{\dd y}{\dd t}+c\,y(t)=0\] The corresponding characteristic equation is \[a\,\lambda^2+b\,\lambda+c=0\]
We restrict ourselves to the case where the discriminant \(D=b^2-4ac\) is equal to zero. Then there is according to the abc-formula only one real root, namely \[\lambda=\frac{-b}{2a}\] The following function is a solution of differential equation \[y_1(t)=e^{\lambda t}\] But are there perhaps more solution? Yes! \[y_2(t)=t e^{\lambda t}\] The general solution of the differential equation can be written as \[\begin{aligned}y(t)&=c_1\,y_1(t)+c_2\,y_2(t)\\\\ &=c_1\,e^{\lambda t}+c_2\, t e^{\lambda t}\\\\ &=(c_1+c_2 t) e^{\lambda t}\end{aligned}\] with constants \(c_1\) and \(c_2\). These constants are determined by boundary conditions.
The discriminant \(D\) of characteristic polynomial \[\lambda^2+6\lambda+9=0\] is equal to \[D=(6\times 6)-(4\times 9) = 0 \] There is one root of the characteristic polynomial, namely \[\lambda= \frac{-6}{2}=-3\] If you had found the equality \[\lambda^2+6\lambda+9=(\lambda+3)^2\] through factorization of a quadratic equation by inspection or a special product had recognized, then this conclusion would have been obvious .
Thus, the differential equation has the following general solution: \[y(t)=(A+B\,t)\,e^{-3t}\] with constants \(A\) and \(B\).
Using the initial values \[y(0)=1, \qquad \frac{\dd y}{\dd t}(0)=-2\] we can define equations that \(A\) and \(B\) must satisfy. Substitution of \(y(0)=1\) in the general solution \(y(t)=(A+B\,t)\,e^{-3t}\) gives \[A=1\] For the usage of the second initial value we need the derivative of the general solution; this can be computed with the calculation rules for differentiating and the derivative of the exponential function: \[y'(t)=B\,e^{-3t}-3(A+B\,t)\,e^{-3t}\] Substitution of \(y'(0)=-2\) gives the equation \[B-3A=-2.\] So we must solve the following system of equations in the unknowns \(A\) and \(B\): \[\left\{\begin{aligned}A &= 1\\ B-3A&= -2\end{aligned}\right.\] The solution of this system of equations is \[A=1 \qquad\text{and}\qquad B=1\] So the solution of the initial value problem is \[y(t)=\left(t+1\right)\e^ {- 3\,t }\]